Heat assisted laser metal deposition of metal matrix composite - Wong, Hao En (Nanyang Technological University, 2022)
The heat assist laser metal deposition (LMD) can be use in future deposition process to successfully reduce cracks occurring in deposits to improve the process reliability. In this phase of the project, we simulate and design a solution to pre-heat the 316L-grade stainless steel substrate top surface to reach 600°C. It is design so that we can have a better control over the temperature that we want to achieve by controlling the power supply to the heating apparatus. We will use NX Siemens program to design and simulate the heating apparatus. The simulation results show that the heating solution will work and be effective in heating up the substrate top surface to 600°C however, the heating solution is still in the middle of production which will exceed our final year project period therefore we conduct the following studies by defocusing the laser to pre-heat the substrate for the following studies. In this studies, laser metal deposition of metal matrix composites (MMC) powders, laser cladding to be specific with tungsten carbide (WC) - reinforce Inconel-718 (INC718) is carry out to compare and study the characteristics with increasing weight percentage of WC from 30% to 100% is mix into INC718 and the effects of pre-heating assistance to prevent cracking of the deposited layer. Thermocouples are tack-weld onto substrate during LMD to study the heat trend during deposition. Post analysis includes liquid penetrant examination (LPE) to identify surface cracks, microstructure analysis with increasing WC weight percentage, and temperature of different points of the substrate can show the heat transfer in the LMD. Future works like repeating the experiments with the completed pre-heating apparatus we design and comparing the results between laser synchronous heating to expand current studies can be done.